One Single Site Clinical Study: To Evaluate the Safety and Efficacy of Immunotherapy With Autologous Dendritic Cells, Cytokine-Induced Killer Cells in Primary Hepatocellular Carcinoma Patients - Xu, Kaiyue; Meng, Zhengjie; Mu, Xiaoxin; Sun, Beicheng; Chai, Yi (Frontiers in Oncology, 2020)
Dendritic cells (DC) and cytokine-induced killer (CIK) cells play an important role in the anti-tumor immune response. In this study, we evaluated the clinical effectiveness of DC/CIK-CD24 immunotherapies to primary hepatocellular carcinoma patients who received radical resection. 36 resected primary hepatocellular carcinoma (HCC) patients were enrolled from August 2014 to December 2015. All patients received 2 or 4 times of DC/CIK immunotherapy after radical resection. 1~4 years patients survival rates were evaluated during the follow-up. The 4-year survival rate of patients who received 2 times of immunotherapy were 47.1%, and the rate of those who received 4 times of immunotherapies were 52.6%, respectively. Compared to baseline, after received the DC/CIK-CD24 autotransfusion, the serum Treg concentration of the patients decreased while CD3+, CD4+, CD56+ increased slightly. The adverse effect of immunotherapy was Ⅰ~Ⅱ° transient fever and could be tolerable. DC/CIK-CD24 immunotherapy can delay the relapse time.